Development of a Halalan Toyyiban warehouse performance measurement system model / Hezlin Shadan - Shadan, Hezlin (2023)
Halalan toyyiban is derived from Arabic and is a state of permissibility for objects oractions according to Syariah (Islamic) law. It implies that humanity is expected to eat, use and act by what is not only permissible (halal) but also good, pure or wholesome(toyyib). Halal products are now widely distributed worldwide and are in demand from Islamic and non-Islamic countries. To ensure the objective of halal logistics to uphold the halal integrity of the entire supply chain from farm to plate achieved, the halal warehouse (HW) plays a pivotal role. Though the general and Halal logistics warehouses share similar objectives to minimise costs, managing the Halal warehouse is more challenging. HW must ensure that all objectives are achieved by prioritizing upholding Halal integrity. The different objectives and additional requirements between conventional and HW can cause conflict in practice and add more issues and challenges to the halal warehouse. More protection and precautionary actions must be involved. The HW needs to control and align the operation with the organisation's objective, halal objective, and halal culture to achieve and improve its performance. This research aims to develop a Halalan toyyiban warehouse performance measurement (HTWPM) system model. Four stages were conducted: background study (S1), exploratory study (S2),development model (S3) and evaluation model (S4) stages. A sequential exploratory mixed-methods was used. Two forms of case studies were completed in the S2. Aqualitative document analysis of the selected input models case study determined the halal warehouse elements from the perspective of halal and toyyib assurance system models. A qualitative thematic analysis of interviews of four halal warehouse companies' case studies delivered halal warehouse elements from the perspective of halal warehouse company's findings. Based on the findings, The HTWPM model was constructed by adapting the balanced scorecard model. The prototype system of the HTWPM model is then developed as an evaluation tool and evaluated for its usability by 22 SMEs. The evaluated HTWPMS closes the gap in understanding how the halal warehouse can measure its organisation's performance. The HTWPMS can be used as a communication tool and can be centred on knowledge aspects in the HW organisation. It can help improve the Malaysian halal industry by gaining confidence and assurances among all related parties. The possibility of further extension or more in-depth empirical research, especially in determining performance indicators recommended for future studies. A web-based information system application is recommended for the system's implementation in the industry so that the performance results can be shared and made available to all stakeholders.